Designing Sustainable Cultural Heritage Souvenirs: Integrating Semioticsand Consumer Preferences in Huishan Ancient Town - Shen, Haijun; Mayusoh, Chanoknart; Inkuer, Akapong; Suwannatat, Permsak (Journal of Cultural Analysis and Social Change, 2026)
Existing souvenir designs often overlook the integration of cultural symbols with consumer preferences, thereby limiting both cultural transmission and market potential. This study combines cultural semiotics with consumer preference analysis to design cultural heritage souvenirs, focusing on Huishan Ancient Town in Wuxi. A mixed-methods approach was adopted, including qualitative interviews (n=12) and observational extraction of cultural symbols, Kano model analysis (n=389) to identify consumer preferences, and prototype design and evaluation (users n=50, experts n=5). The results identified six major symbols, including the "Afu" clay figurine, confirming that heritage value (β=0.40) and hedonic value (β=0.28) are key drivers of purchase intention. The "Huishan Clay Figurine Car Aroma Pendant" prototype integrated the "Afu" symbol with invigorating essential oils, meeting functional needs (M=35.7%) and traditional symbol expectations (O=40.0%), and received high evaluations (expert ratings = 7.9–9.1), although color optimization is needed. This study proposes a "Cultural Symbol–Consumer Preference" framework, extending the systematic application of cultural semiotics in design and enriching the attribute classification of the Kano model in cultural tourism contexts, thereby providing a replicable paradigm for cultural conservation and sustainable tourism development in heritage sites like Huishan Ancient Town.